INCLUSION OF SUSTAINABLE DEVELOPMENT CONTENT IN ENGLISH TEXTBOOKS OF SECONDARY LEVEL: AN ANALYTICAL STUDY - Kumar, Sarvesh; Arora, Santosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sustainable development is crucial to the solution of the interrelated threats of the 21st century-a triple threat of environmental, social, and economic. Learning about sustainability is important to each learner, and textbooks act as a critical source of learning for this purpose. The representations of the SD concepts in the English NCERT textbooks for Grades IX (Beehive) and X (First Flight) were explored with the objective of evaluating their appropriateness to the ESD framework. Using a qualitative content analysis approach, this study examines the textbooks of secondary level of English subject in terms of environmental, social, and economic perspectives on sustainability. Literary works, poems, and narrative prose are analysed to evaluate the implicit and explicit inclusion of SD themes like climate change, conservation, gender equality, and economic equity. The effectiveness of associated exercises and activities in promoting critical thinking and action-oriented learning is also reviewed. The findings reveal that SD themes are present but are predominantly implicit, with a greater emphasis on environmental aspects compared to social and economic dimensions. Pedagogical opportunities to connect textual content with practical sustainability issues are often underutilized. Exercises and activities encourage reflective thinking but rarely draw direct links to global challenges such as climate change or poverty alleviation.